Mean-Variance Portfolios' Optimization between "Safety-First" Criterions and "Downside Risk" Measures (Journal of Hama University, 2021)
This study aimed to evaluate the effectiveness of relying on the (Mean-Variance) model to construct portfolios according to the investors' attitudes towards risk, depending on the historical data represented in the daily closing price series of shares for all companies listed on the Damascus Stock Exchange during the period from 1/1/2019 to 7/31/2019 2020. The research concluded that using the (M-V) model produced portfolios fit the investor's risk tolerance. The results of applying the (M-V) were close to the safety-first criterions application results, as indicated by the use of semi-variance as a measure of risk, its low values ​​compared to the variance values, which indicated that most of the volatilities in the returns of shares and portfolios of listed companies In the DSE, is in a positive direction, that is, it is the result of the increase in stock closing prices from one period to the next. When comparing the application results with the (M-V) model, the convergence between them was observed. It also became clear when reviewing the CVaR, whether for stocks or portfolios, that they are relatively low, indicating that the expected loss values ​​with a (5%) probability were low, and this is consistent with the level of returns achieved for all stocks in DSE, as for the portfolios. The results were consistent with the semi-variance as well as safety-first criterions, hence the investor's portfolio of risk aversion can be considered the optimum among the group of portfolios and the most suitable for application in DSE.